Electromagnetic tracking for femoral derotation osteotomy: an in vivo study - Geisbüsch, Andreas; Auer, Christoph; Dickhaus, Hartmut; Putz, Cornelia; Dreher, Thomas (Journal of orthopaedic research, 2017)
Femoral derotation osteotomy delivers good to excellent results in the treatment of rotational gait abnormalities and especially in internal rotation gait. The outcome of the procedure has been evaluated in numerous short- and long-term studies. Although reasons for recurrence and over-/under-correction have been unveiled in earlier studies the mechanisms are still not fully understood. False intra-operative assessment of the derotation angle may contribute to imprecise outcomes. In a recent saw-bone study we evaluated an electromagnetic tracking system in comparison to conventional goniometer measurement and a CT reference measurement and found it to be extremely accurate, whereas the use of a conventional goniometer for derotation measurement showed a high inter- and intra-rater variability. The current study evaluates the electromagnetic tracking system for continuous intra-operative derotation control under real OR conditions. Adults (age: 18-40 years) with the diagnosis of internal rotation gait, independent of the underling pathology, undergoing a supracondylar deroation osteotomy were included. A rotational CT scan was conducted before and in close proximity after surgery and the difference served as reference for the electromagnetic tracking results. The results showed a mean deviation of 2.6° (1.2-5.5°) in comparison to the reference measurement of the pre- and post-operative CT scans. The system proved to be stable under OR conditions with a good usability and a small technical footprint. Electromagnetic tracking delivers a precise, reliable, and independent assessment of intra-operative derotation angles in femoral derotation osteotomies. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2652-2657, 2017.
Gesehen am 27.04.2018